Purpurogemutantin and Purpurogemutantidin, New Drimenyl Cyclohexenone Derivatives Produced by a Mutant Obtained by Diethyl Sulfate Mutagenesis of a Marine-Derived Penicillium purpurogenum G59 - Wen-Cai Ye; Zhi-Jun Zhang; Li Li; Xiao-Jun Huang; Shi-Ming Fang; Chang-Wei Li; Chang-Jing Wu; Cheng-Bin Cui (Marine Drugs, 2012)
Two new drimenyl cyclohexenone derivatives, named purpurogemutantin (1) and purpurogemutantidin (2), and the known macrophorin A (3) were isolated from a bioactive mutant BD-1-6 obtained by random diethyl sulfate (DES) mutagenesis of a marine-derived Penicillium purpurogenum G59. Structures and absolute configurations of 1 and 2 were determined by extensive spectroscopic methods, especially 2D NMR and electronic circular dichroism (ECD) analysis. Possible biosynthetic pathways for 1–3 were also proposed and discussed. Compounds 1 and 2 significantly inhibited human cancer K562, HL-60, HeLa, BGC-823 and MCF-7 cells, and compound 3 also inhibited the K562 and HL-60 cells. Both bioassay and chemical analysis (HPLC, LC-ESIMS) demonstrated that the parent strain G59 did not produce 1–3, and that DES-induced mutation(s) in the mutant BD-1-6 activated some silent biosynthetic pathways in the parent strain G59, including one set for 1–3 production.